Analysis of Cement Fiber Machine Maintenance Using the PMMS (Preventive Maintenance Management System) Method at PT. Nusantara Building Industries - Labib Mumtaza Rabani; Akhmad Syakhroni (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Effective machine maintenance is essential for ensuring production continuity in the fiber cement industry, where high-capacity equipment operates continuously under demanding production conditions. This study analyzes the maintenance performance of cement fiber production machines at PT. Nusantara Building Industries using the Preventive Maintenance Management System (PMMS). An empirical case study approach was employed by collecting data through direct observation, semi-structured interviews, and documentation of maintenance records, PMMS forms, inspection checklists, and downtime reports during the internship period. Machine reliability was evaluated using Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), Pareto analysis, and Fishbone analysis to identify critical equipment and dominant failure causes. The results indicate substantial variations in operational reliability among production machines, with FS6 and FS7 exhibiting the highest downtime and failure frequencies. Pareto analysis revealed that a limited number of failures contributed to most cumulative downtime, while Fishbone analysis identified machine condition, maintenance methods, human factors, environmental conditions, materials, and measurement practices as the principal causes of recurring failures. Reliability-based preventive maintenance scheduling within the PMMS framework established maintenance intervals according to equipment criticality, enabling more effective maintenance planning and resource allocation. The proposed PMMS approach improves maintenance decision-making, enhances equipment reliability, supports production continuity, and provides a practical framework for data-driven maintenance management in continuous manufacturing systems.